2020
DOI: 10.3390/ijms21207749
|View full text |Cite
|
Sign up to set email alerts
|

Brucella Genomics: Macro and Micro Evolution

Abstract: Brucella organisms are responsible for one of the most widespread bacterial zoonoses, named brucellosis. The disease affects several species of animals, including humans. One of the most intriguing aspects of the brucellae is that the various species show a ~97% similarity at the genome level. Still, the distinct Brucella species display different host preferences, zoonotic risk, and virulence. After 133 years of research, there are many aspects of the Brucella biology that remain poorly understood, such as ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
28
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 176 publications
7
28
0
1
Order By: Relevance
“…Phage proteins, insertional sequences predicted in accessory genome, and prophages predicted in the individual genome may have a role in the diversity of B. melitensis . Suárez-Esquivel et al (2020) reported that insertional sequences in Brucella spp. may have a role in diversity within the species.…”
Section: Core and Accessory Gene Compositionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phage proteins, insertional sequences predicted in accessory genome, and prophages predicted in the individual genome may have a role in the diversity of B. melitensis . Suárez-Esquivel et al (2020) reported that insertional sequences in Brucella spp. may have a role in diversity within the species.…”
Section: Core and Accessory Gene Compositionsmentioning
confidence: 99%
“…The B. melitensis genome is conserved since there is no other extrachromosomal material (plasmids), and there is limited report about the horizontal gene transfer, which may be due to its intracellular survival. So the other possible mechanism for the evolution of B. melitensis may be mutations so as to survive in a new geographical region and also to survive in a new host ( Tan et al, 2015 ; Suárez-Esquivel et al, 2020 ). Hence, identifying the SNPs can enable to know the evolution of B. melitensis strains.…”
Section: Core and Accessory Gene Compositionsmentioning
confidence: 99%
“…Brucellosis remains endemic in many parts of the world, including the Middle East, Africa, Latin America, Central Asia, and several regions of the Mediterranean [ 1 , 2 , 3 , 4 ]. Brucella melitensis , Brucella abortus, and Brucella suis are the most important members of the genus because they are responsible for the human disease [ 5 , 6 ] and for significant economic losses in livestock [ 7 , 8 ], while Brucella canis , Brucella neotomae , and Brucella ovis display less or non-zoonotic potential [ 9 ]. Recently, many other species have been described in aquatic mammals (like Brucella pinnipedialis and Brucella ceti ) and other wildlife such as Brucella papionis , Brucella microti , Brucella inopinata, and Brucella vulpis [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The infection in farmed animals usually manifests itself as spontaneous abortions and infertility. The Brucella genus has recently expanded from six to 11 species, all of which are associated with mammals ( Soler-Llorens et al, 2016 ; Suarez-Esquivel et al, 2020 ). Among all Brucella species, B .…”
Section: Introductionmentioning
confidence: 99%